Communicative-pragmatic paradigm: the importance and opportunities for the formation of speech culture (Eurasian Journal of Philology Science and Education, 2021)
The introduction outlines the communicative-pragmatic paradigm, which is a new, relevant direction, these ideas are based on the work of the intellectuals of the nation at the beginning of the twentieth century. The opinion of thinkers of different periods is argued that the improvement шт the culture of the younger generation personality, the culture of the word in the educational process allows to form its civic appearance, national consciousness and mentality. The goal of the article is to consider the issues of the formation the culture of a person's pronunciation, the components of speech activity are comprehensively differentiated - the peculiarities of pronunciation. In this regard, the effectiveness of the use of the communicative-pragmatic method in mastering the skills of oral text formation has been scientifically substantiated.The authors of the article are participants in the project "Paradigms of language communication: literary pronunciation and Latin American writing." Therefore, the article also contains the findings of the research within the framework of this project. During the experiment, students are offered to work with a structural diagram of the  oral speech development for the analysis of a specific article. It is proved that students, acquiring such a specific orientation, acquire speech skills characteristic of the communicative quality of oral speech culture in accordance with the communicative-pragmatic paradigm, the achieved results are listed.It is differentiated that the right compilation, indication of the structural and content parts of monologue texts and the correct use of the paragraph in the transmission of the main idea when teaching the speaker the culture of pronunciation is one of the main conditions for achieving a communicative goal. It is assumed that the indicator of the communicative quality of a word is not limited only to the text, but also one of the main non-linguistic conditions of the participle is the addressee factor.Keywords: communicative-pragmatic paradigm, pronunciation, literary speaking, speech culture, norms of literary language, language communication, text, conversational activity